GE_GERICHTE P/7970/2016 vom 22. Mai 2019 - GE Cour de justice (2019)
DÉFENSE D'OFFICE ; INDEMNITÉ(EN GÉNÉRAL) ; FORFAIT ; TARIF(EN GÉNÉRAL) ; DÉPLACEMENT(SENS GÉNÉRAL) ; INTÉRÊT MORATOIRE | CPP.135.al1; Cst.29.al2; RAJ.16; RAJ.23